PERBAIKAN RANCANGAN MESIN PENCACAH PLASTIK DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) DAN DESIGN FOR MANUFACTURE AND ASSEMBLY (DFMA) - Gusman, Taufan Tama; Ginting, Rosnani; Ishak, Aulia (Jurnal Ilmiah Teknik Industri, 2025)
CV. XYZ is a private company that operates in the manufacturing sector of machinery manufacturing, one of its products is Plastic Machinery. There is a problem in its manufacturing process, which is a long assembly time and a high assembling cost. The study aims to design a simpler design proposal for repairs of plastic milling machines using integrated concepts of Quality Function Deployment and Design for Manufacture and Assembly. (DFMA). Identification of problems in this research is carried out using the Quality Function Deployment method and developed using the DFMA (Design for Manufacture and Assembly) method to evaluate or improve the product. Based on the phase I QFD method, the attributes of technical characteristics are assembly time, component cost, number of components, assembling cost, and design efficiency, Easy of Manufacturing and Durability. Then, in Phase II QFD, two attributes were obtained from three critical parts: Upper body and lower body machine. After that, the improvement of the design of the product of the plastic grinding machine with the DFMA method was achieved reducing the assembly time by 1038 minutes, then improving the design efficiency by 1.9% and saving assembling costs of Rp 249,277.00